1976
DOI: 10.3109/00498257609151633
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent Pharmacokinetics of Laevodopa and its Metabolites in the Rat

Abstract: 1. Plasma levels of total radioactivity, unchanged laevodopa, dopamine, 3-O-methyldopa and non-amino phenolic acids were measured in rats treated orally with [3H]laevodopa at total laevodopa doses of 1, 10, 20 and 100mg/kg while the radioactive dose was maintained at 100muCi/kg for all animal groups. 2. Within the dosage range studied, non-linear pharmacokinetics were observed for unchanged laevodopa, non-amino phenolic acids and dopamine but not for 3-O-methyldopa. 3. The area under the plasma concentration-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…The dose-dependency of L-dopa and dopamine appearances in the vascular perfusate is consistent with the kinetics observed in-vivo after oral administration of L-dopa to rat (Cheng & Fung 1976), dog and man (Sasahara et all980). In these experiments the area under the plasma concentration time curves (AUC) for L-dopa was found to increase nonlinearly with the dose.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The dose-dependency of L-dopa and dopamine appearances in the vascular perfusate is consistent with the kinetics observed in-vivo after oral administration of L-dopa to rat (Cheng & Fung 1976), dog and man (Sasahara et all980). In these experiments the area under the plasma concentration time curves (AUC) for L-dopa was found to increase nonlinearly with the dose.…”
Section: Discussionsupporting
confidence: 86%
“…In the rat the contribution of the gut wall to the overall first-pass effect of L-dopa appeared to be greater than that of the liver (Iwamoto et a1 1987). Following oral administration of L-dopa to man, dog (Sasahara et al 1980) and rat (Cheng & Fung 1976) dosedependent pharmacokinetics were observed. In addition, competition for absorption by other amino acids may occur.…”
mentioning
confidence: 99%
“…High oral doses of levodopa appear to be necessary to saturate gastro-intestinal oral levodopa dosage, the bio-availability of levodopa in the plasma, as indicated by plasma time-concentration curves, shows an exponential rise. (16).…”
Section: Levodopa Absorptionmentioning
confidence: 99%